Maternal and foetal outcome of hypothyroidism in pregnancy: a prospective observational study - Kulkarni, Neha S.; Jadhav, Balaji J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Thyroid dysfunction is one of the most common endocrine disorders affecting women of reproductive age group. There is a debate among obstetricians about universal versus targeted screening for hypothyroidism during pregnancy. Therefore, we conducted this study with aim to highlight the need for universal screening of pregnant women for hypothyroidism. Methods: This was prospective analytical study involving 200 pregnant women conducted in a tertiary care hospital in Mumbai from January 2018 to December 2019. Thyroid-stimulating hormone (TSH) was done as a screening test. Estimation of free T3 (FT3) and free T4 (FT4) are advised if TSH was found abnormal. Patients were followed up throughout the pregnancy and postpartum up to 6 weeks. Study parameters were assessed in both mother and neonate and statistical analysis was done. Results: Pregnancy induced hypertension (PIH) was observed in 13% of study population. Premature labour was observed in 11% of study population. Recurrent abortion was observed in 7% of study population. Postpartum haemorrhage (PPH) was observed in 4% of study population. Anaemia was observed in 69% of study population. Neonatal intensive care unit (NICU) admission was observed in 17% of study population. Neonatal hypo/ hyperthyroidism was observed in 3% of study population. Conclusions: Pregnant females should routinely be screened for thyroid functions to detect hypothyroidism and be given adequate treatment to prevent maternal and foetal complications. Adequate treatment and regular follow up will improve the maternal and foetal outcomes.